Neurotransmitter receptor availability in the rat brain is constant in a 24 hour-period. (9th August 2017) - Oskamp, A.; Wedekind, F.; Kroll, T.; Elmenhorst, D.; Bauer, A.
ABSTRACT: Wakefulness and sleep are fundamental characteristics of the brain. We, therefore, hypothesized that transmitter systems contribute to their regulation and will exhibit circadian alterations. We assessed the concentration of various neurotransmitter receptors and transporters including adenosinergic (A1 AR, A2A AR, and ENT1), dopaminergic (D1 R, D2 R, and DAT), and serotonergic (5-HT2A R) target proteins. Adult male Sprague Dawley rats were used and maintained in a 12 h light: 12 h dark cycle (lights on from 07:00 h to 19:00 h). We measured receptor and transporter concentrations in different brain regions, including caudate putamen, basal forebrain, and cortex in 4 hour-intervals over a 24 hour-period using quantitative in vitro autoradiography. Investigated receptors and transporters showed no fluctuations in any of the analyzed regions using one-way ANOVA. Only in the horizontal diagonal band of Broca, the difference of A1 AR concentration between light and dark phases ( t -test) as well as the cosinor analysis of the 24 hour-course were significant, suggesting that this region underlies receptor fluctuations. Our findings suggest that the availability of the investigated neurotransmitter receptors and transporters does not undergo changes in a 24 hour-period. While there are reports on changes in adenosine and dopamine receptors during sleep deprivation, we found no changes in the investigated adenosine, dopamine, and serotonin receptors during regular and undisturbed day-night cycles.